Birokrasi dan Hoax: Studi Upaya Menjaga Netralitas Aparatur Sipil Negara di Era Post-Truth: Bureaucracy and Hoax: Study of Effort to Maintain the Neutrality of Public Servants in The Post-Truth Era - Faedlulloh, Dodi; Duadji, Noverman (Jurnal Borneo Administrator, 2019)
The relationship between bureaucracy and politics is important to discuss again after Indonesia experienced the heated atmosphere of the 2019 elections. The political situation that created polarization had shaken the neutrality of the public servants (ASN). There is an ASN who openly declares political preferences while simultaneously spreading hoaxes in the public sphere. This is because of factors other than the political temperature, also the post-truth phenomenon which also attacked Indonesia. This study was conducted to revisit the discourse on the importance of bureaucratic neutrality to maintain performance in public services and care for democracy. The writer used the desk study method by collecting data and information based on examining and analyzing secondary data. The results emphasized the importance of re-maintaining neutrality for ASN. The alternative step to maintain the ASN neutrality is collaborative supervision conducted by various elements of government and society. In addition, this study offers the importance of ASN being given critical, scientific and literacy education to stem hoaxes in a bureaucratic environment. The ASN can also actively take part in building an anti-hoax community in the bureaucratic environment so that the ASN continues to know of responding to the hoax phenomenon. Keywords: Bureaucracy, Hoax, Neutrality, Elections, Post-Truth Abstrak Relasi antara birokrasi dan politik kembali penting didiskusikan pasca Indonesia mengalami suasana pemilu 2019 yang panas. Situasi politik yang menciptakan polarisasi sempat mengguncang netralitas aparatur sipil negara (ASN). Ada oknum ASN yang secara terbuka mendeklarasikan preferensi politik sekaligus turut menyebarkan hoax di ruang publik. Hal ini disebabkan selain faktor suhu politik yang panas, juga fenomena post-truth yang turut menyerang Indonesia. Studi ini dilakukan untuk menengahkan kembali diskursus tentang pentingnya netralitas birokrasi untuk menjaga kinerja dalam pelayanan publik serta yang juga penting adalah merawat demokrasi. Dalam proses penulisan artikel ini, penulis menggunakan metode desk study, yaitu dengan mengumpulkan data dan informasi berbasiskan pada pemeriksaaan dan analisis data dan informasi yang menggunakan data sekunder yang aktual. Hasil dari studi ini menekankan tentang pentingnya kembali menjaga netralitas bagi ASN. Adapun alternatif langkah yang bisa dilakukan agar netralitas ASN tetap terjaga, yakni dengan pengawasan kolaboratif yang dilakukan pelbagai elemen dari pemerintah dan masyarakat. Selain itu, studi ini menawarkan pentingnya para ASN dibekali dan membekali diri pendidikan kritis dan ilmiah serta pendidikan literasi untuk membendung hoax di lingkungan birokrasi. Para ASN juga bisa berperan aktif dalam membangun komunitas anti-hoax di lingkungan birokrasi agar para ASN terus aware dalam merespon fenomena hoax. Kata Kunci: Birokrasi, Hoax, Netralitas, Pemilu, Post-Truth